Interaction of Aluminum Metaphosphates in the Setting of Potassium Silicate Solutions in Terms of the Crystalline Phase Composition. Issue 5 (28th May 2020) - Masoudi Alavi, Ali; Sax, Almuth; Quirmbach, Peter
Abstract: Aluminum phosphates are known as inorganic hardening agents for the setting of alkali silicate solutions, but only few studies have been published on the setting mechanism of potassium water glass. The solution behavior of two aluminum metaphosphates in alkaline environments were investigated photometrically determining the dissolved aluminum content. The crystalline phase composition of the hardened potassium silicate systems was determined by X‐ray diffraction. New insights into the setting mechanism were obtained concerning the structure of the aluminum metaphosphate and the SiO2 /K2 O ratio of three different potassium silicate solutions. With increasing pH value aluminum tetrametaphosphate reacts rapidly and forms crystalline potassium tetrametaphosphate dihydrate by an ion‐exchange‐reaction. In parallel, a depolymerization of the cyclic metaphosphate structure occurs leading to potassium dihydrogen phosphate as final fragmentation product. With aluminum hexametaphosphate no ion‐exchange reaction product was observed. Only potassium dihydrogen phosphate could be found in higher quantities compared to the reaction with aluminum tetrametaphosphate. Abstract : Insights on potassium silicates : Mechanism of the chemically initiated hardening of potassium silicate solutions with aluminum metaphosphates. Ion‐exchange reaction, depolymerization of the cyclic metaphosphate structures, and polycondensation of the amorphous alumosilicate binder matrix. Investigation of the dissolution behavior of aluminum metaphosphates in alkaline environment. Description of the crystalline phase composition.